Kegawatdaruratan Bedah Abdomen Anak di Rumah Sakit Islam Banjarnegara Selama Pandemi Covid-19 - Mirza Nuchalida; Agus Ujianto; Niko Yuandi (Jurnal Health Sains, 2021)
Children's Abdominal Surgery Emergency is calculated 2.4-3.1% in child cases. The cause of a child's abdominal surgery emergency is very common and difficult to treat. The object in this study was applied to the Secondary Hospital in Banjarnegara Islamic Hospital with existing patterns and results. Medical record method of children aged 1 year to 16 years who are hospitalized with abdominal surgery in children at Banjarnegara Islamic Hospital, between 2018 to March 2021 retrospectively. The results of the study there were 40 children aged 1 month to 16 years in this study. 25 males and 15 females. The average age is 10 years while the length of hospitalization is 4.5 days 25 patients (62.5%) diagnosed within 24 hours, 11 patients (27.5%) in therapy after 24 hours to 48 hours, and 4 patients (10%) in therapy within > 48 hours. abdominal trauma 1 child (3,25%), intususepsi 3 children (7,5%), inguinal hernia 2 children (3,125%), intestinal obstruction 5 children (12,55%), appendicitis perforation 13 children (32,5%), and acute appendicitis 16 children (40%). 39 children (97.5%) complications after surgery. The average complication is infection and appendication perforation occurs with a value (p: 0.05). There are no deaths in this case. The conclusion in this study, acute appendicitis is the most common cause in the treatment of childhood abdominal surgery emergency in islamic hospitals banjarnegara. This illustration has patterns and results.